Wavelet Packet Transform Based Power Quality Analysis - OBED, Adel A. (Basrah Journal for Engineering Sciences, 2012)
This paper presents a diagnostic technique for power quality analysis against different disturbances in electrical power source. The presented technique utilizes a wavelet packet transform (WPT)-based a proposed algorithm for monitoring and detection various disturbances occurring in supply voltage signal and in supply frequency. The values and the time locations for low and high frequency coefficients are determined up to level six and compared with a threshold determined from the operation of healthy source. The proposed technique is tested on certain cases and the simulated results indicate that this technique is effective for detecting and monitoring different mentioned disturbances.